Socio-economic Factors Contributing to Reverse Migration and Its Impacts on the Local Economy - Khadka, Bimal Kumar; Bhattarai, Rudra Prasad; Chuwan, Nar Kumar; Bhatt, Roshan (Journal of Advanced Academic Research, 2026)
Reverse migration has turned out to be a major socio-economic phenomenon in Nepal, especially after world labour market shake up, increase in cost of living in overseas place and shifting individual and family priorities. Although research in the literature of migration has focused greatly on labor mobility towards the receiving country, very little is known about the motivations of such moves, experiences of reintegration and the effect that such a movement has on the local economy. This paper evaluates the reasons of backward migration which are socio-economic and analyses the presumed effects of the returning population on Kathmandu Valley economy. The research design executed in the study is exploratory qualitative research. The 22 Nepal return migrants were interviewed using snowball sampling in semi-structured in-depth interview transforming the selected interviewee into the sample. The data was analyzed by themes to obtain the lived experiences of the returnees, the driving factors behind the reasons of returning, challenges of re-integration, and economic participation after returning. Results show that even though overseas migration provided career advancement and financial benefits, emotional loneliness, immigration regulations, insecurity in jobs, and family commitments influenced greatly the decision to move back. The returnees helped in the local economic activities, including entrepreneurship, creation of jobs, payment of taxes and transfer of skills. The paper concludes that reverse migration in Nepal is a multidimensional phenomenon, which is defined by individual agency and structural conditions interaction. There should be policy interventions that recognize the skills of return migrants, reintegrate them, and help generate entrepreneurship to ensure that the developmental potential of the return migrants is maximized.